In situ synthesis of a novel metal oxide affinity chromatography affinity probe for the selective enrichment of low‐abundance phosphopeptides - Wang, Baichun; Wu, Huanming; Yan, Yinghua; Tang, Keqi; Ding, Chuan‐Fan (Rapid communications in mass spectrometry, 2020)
Rationale Due to the dynamic nature of phosphorylation states and the low stoichiometry of phosphopeptides, it is still a challenge to efficiently capture phosphopeptides from complex biological samples before mass spectrometry analysis. Among the enrichment strategies, metal oxide affinity chromatography (MOAC) is one of the most widely used and the one with the most potential. It is based on reversible Lewis acid–base interactions between the metal oxides and the negatively charged phosphate groups to achieve the specific selection of phosphopeptides. Methods A novel MOAC affinity probe, denoted as G@PDA@ZrO2, was successfully synthesized by in situ grafting ZrO2 onto the surface of graphene (G) modified with polydopamine (PDA). The novel MOAC probe thus obtained was used for phosphopeptide enrichment. Results This novel MOAC affinity probe when used to selectively enrich phosphopeptides from standard protein digest solutions exhibited a high selectivity (β‐casein:bovine serum albumin = 1:1000), a low detection limit (4 fmol), and a high loading capacity (400 mg/g). At the same time, the experimental results proved that G@PDA@ZrO2 had great recyclability (five cycles), stability, and reproducibility. Subsequently, G@PDA@ZrO2 was applied to enrich phosphopeptides from human saliva and human serum, in which 25 and 4 phosphopeptide peaks, respectively, were detected. Conclusions This novel MOAC affinity probe (G@PDA@ZrO2) showed good performance in enriching phosphopeptides. Thus, G@PDA@ZrO2 has good potential in phosphopeptidomics analysis.